Post-acute care disparities in total joint arthroplasty - Lan, Roy H. (Arthroplast Today, 2017)
BACKGROUND: Understanding the socioeconomic factors that influence hospitalization and post-discharge metrics after joint replacement is important for identifying key areas of improvement in the delivery of orthopaedic care. METHODS: An institutional administrative data set of 2869 patients from an academic arthroplasty referral center was analyzed to quantify the relationship between socioeconomic factors and post-acute rehabilitation care received, length of stay, and cost of care. The study used International Classification of Disease, ninth edition coding in order to identify cohorts of patients who received joint arthroplasty of the knee and hip between January 2007 and May 2015. RESULTS: The study found that females (odds ratio [OR], 2.07; 95% confidence interval [CI], 1.74-2.46), minorities (OR, 2.11; 95% CI, 1.78-2.51), and non-private insurance holders (OR, 1.56; 95% CI, 1.26-1.94) were more likely to be assigned to institutional care after discharge. The study also found that minorities (OR, 1.45; 95% CI, 1.24-1.70) and non-private insurance holders (OR, 1.43; 95% CI, 1.16-1.77) are more likely to exhibit longer length of stay. Mean charges were higher for males when compared to females ($80,010 vs $74,855; P < .001), as well as total costs ($19,910 vs $18,613; P = .001). CONCLUSIONS: Socioeconomic factors such as gender, race, and insurance status should be further explored with respect to healthcare policies seeking to influence quality of care and health outcomes.